River Capacity and Pump Requirements for Flood Prevention in Urban Areas - Sutrisno, Tri; Prawito, Adi; Setiawan, Muhammad Ikhsan (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Floods are one of the natural disasters that often threaten human lives and assets in urban areas. Factors such as climate change, rapid urbanization, and land changes can increase the risk of flooding. Pesawahan Village, located in the Porong District, Sidoarjo Regency, is one of the areas that frequently experiences flooding issues. Floods in this village can endanger the lives of the community, agricultural land, and essential infrastructure. To reduce the risk of flooding and protect valuable resources, in-depth research is needed on the capacity of the river passing through Pesawahan Village and the requirements for a pump system for flood prevention. Pesawahan Village is situated in low-lying terrain and is close to a significant river or water channel. This topographical and geographical condition makes the village vulnerable to flooding, especially during intense rainy seasons. The area often experiences high rainfall during the rainy season, leading to river overflow and subsequent flooding. Population growth and infrastructure development in Pesawahan Village can alter the water flow patterns and reduce the river's capacity, exacerbating the risk of flooding. A pump system is one effective solution to mitigate the risk of flooding in urban and rural areas. However, to design and operate an efficient pump system, a good understanding of the river's capacity and water flow characteristics in the area is essential.